Pemberian Bahan Organik Kompos Jerami Padi dan Abu Sekam Padi dalam Memperbaiki Sifat Kimian Tanah Ultisol Serta Pertumbuhan Tanaman Jagung - Maulana Azomy Pane; M. M. B. Damanik; Bintang Sitorus (Universitas Sumatera Utara, 2014)
The Objective of this study is determine the effect of rice straw compost and rice ash on somechemical properties of Ultisol and its effect on the growth of corn plants. The research was done ingauze house and Research and Technology Laboratory, Agricultural Faculty, University of NorthSumatera, Medan from May until July 2013. The study used randomized block design consits of twofactors with three replications. The first factor are rice sraw compost consist of four dosage level(g/5 kg dry oven soil weight) : K0 (0), K1 (25), K2 (50), K3 (75) and the second factore are rice ashconsist of four dosage level (g/5 kg dry oven soil weight) : M0 (0), M1 (10), M2 (20), M3 (30).Theresults showed that the effect of aplication of rice straw compost significantly increased soil Corganic,P-available, plant height, dry weight of a plant, plant N uptake, and plant P uptake but notsignificantly effect the soil pH and N-total of soil, aplication of rice ash significantly increased soilC-organic and plant N uptake but not significantly increased the soil pH, P-available, N-total of soil,plant hight, dry weight plant and plant P uptake.Keyword: ultisol, rice straw compost, rice ash